Central bank misperceptions and the role of money in interest rate rules - Guenter Beck; Volker Wieland (National Bank of Belgium, 2008)
Research with Keynesian-style models has emphasized the importance of the output gap for policies aimed at controlling inflation while declaring monetary aggregates largely irrelevant. Critics, however, have argued that these models need to be modified to account for observed money growth and inflation trends, and that monetary trends may serve as a useful cross-check for monetary policy. We identify an important source of monetary trends in form of persistent central bank misperceptions regarding potential output. Simulations with historical output gap estimates indicate that such misperceptions may induce persistent errors in monetary policy and sustained trends in money growth and inflation. If interest rate prescriptions derived from Keynesian-style models are augmented with a cross-check against money-based estimates of trend inflation, inflation control is improved substantially.
Keywords: E32; E41; E43; E52; E58; 330; monetary policy under uncertainty; money; output gap uncertainty; quantity theory and Taylor rules; Geldpolitik; Produktionspotenzial; Zinspolitik; Quantitätstheorie; Taylor-Regel; Theorie